Pengaruh Kualitas Pelayanan Karyawan dan Fasilitas Kamar Terhadap Loyalitas dengan Variabel Kepuasan Sebagai Variabel Mediasi Sebuah Studi Kasus Pada Hotel Benteng Kota Bukittinggi - Nabila Ufairah; Pasar Ibu (Lembaga Pengembangan Kinerja Dosen, 2025)
This research purposes it to reveal the extent of the influence of service quality and room facilities at Hotel Benteng Kota Bukittinggi on loyalty, with satisfaction as a variable of mediating. This research type uses a method by quantitative descriptive with an approach by causal associative (cause and effect) through survey methods. The sample used comprises 93 samples. Service Quality (X1), Room Facilities (X2), Loyalty (Y), and Guest Satisfaction (Z) are all in the moderate category, with respective scores of 3.95, 3.81, 4.01, and 4.07. Data were analyzed utilized descriptive statistics and SEM (PLS). Hypotheses were tested using t-statistics and p-values. If the t-statistic exceeds the t-table or the p-value does not exceed 0.05, then the hypothesis is confirmed. Research findings show that variable X1 does not affect variable Z (t-statistic 0.041) and variable Y (t-statistic 0.192). Furthermore, variable Z (t-statistic 6.449) and variable Y (t-statistic 4.872) are significantly influenced by variable X2. Next, variable Z shows a strong impact on variable Y, as evidenced by its t-statistic value of 3.313. In addition, it shown that, through t-statistic 0.040 for variable X1 and 2.447 for variable X2, variable X1 does not have an impact in significant to variable Y through variable Z. On the contrary, variable X2 has an impact in significant to variable Y through variable Z. Thus, only the hypothesis related to variable X2 can be accepted in this research.